MicroRNAses and the regulated degradation of mature animal miRNAs - Grosshans, Helge; Chatterjee, Saibal (Advances in experimental medicine and biology, 2010)
microRNAs (miRNAs) are small noncoding RNAs that regulate numerous target mRNAs through an antisense mechanism. Initially thought to be very stable with half-lives on the order of days, mature miRNAs have recently been shown to be subject to degradation by 'microRNases' (miRNases) in plants (the small RNA degrading nucleases, SDN) and animals (exoribonuclease 2/XRN-2/XRN2). Interference with these miRNA turnover pathways causes excess miRNA activity, consistent with an important contribution to miRNA homeostasis. Moreover, it is now emerging that long half-lives are not an invariant feature of miRNAs but that marked differences exist in the stabilities of individual miRNAs and that cellular states can further determine miRNA turnover rates. Although the means of regulation are still largely unclear, biochemical data suggest that target mRNA-binding can stabilize miRNAs within their Argonaute (AGO) effector complexes, providing one possible mechanism that may control miRNA half-lives. We will summarize here what is known about miRNA turnover in animals and how recent discoveries have established a new dynamic of miRNA-mediated gene regulation. We will highlight some of the open questions in this emerging area of research.